1985
DOI: 10.1068/p140721
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Visual Capture: Apparent Auditory Motion Induced by a Moving Visual Target

Abstract: Apparent motion of a sound source can be induced by a moving visual target. The direction of the perceived motion of the sound source is the same as that of the visual target, but the subjective velocity of the sound source is 25-50% of that of the visual target measured under the same conditions. Eye tracking of the light target tends to enhance the apparent motion of the sound, but is not a prerequisite for its occurrence. The findings are discussed in connection with the 'visual capture' or 'ventriloquism' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 13 publications
6
43
0
Order By: Relevance
“…Over a number of studies, participants were shown to be significantly less accurate in judging the direction of auditory motion on conflicting trials (i.e., ones in which the auditory and the visual stimuli moved in opposite directions) than on congruent trials (i.e., ones in which the auditory and the visual stimuli moved in the same direction). The existence of this cross-modal dynamic capture effect is consistent with a number of previous findings reported in the experimental literature (e.g., Mateeff, Hohnsbein, & Noack, 1985).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Over a number of studies, participants were shown to be significantly less accurate in judging the direction of auditory motion on conflicting trials (i.e., ones in which the auditory and the visual stimuli moved in opposite directions) than on congruent trials (i.e., ones in which the auditory and the visual stimuli moved in the same direction). The existence of this cross-modal dynamic capture effect is consistent with a number of previous findings reported in the experimental literature (e.g., Mateeff, Hohnsbein, & Noack, 1985).…”
supporting
confidence: 81%
“…Whereas some researchers have argued that visual dynamic stimuli have a strong influence on the perception of auditory motion (e.g., Mateeff et al, 1985;Zapparoli & Reatto, 1969), others have come to the opposite conclusion, arguing instead that visual dynamic Several studies have shown that the direction in which a visual apparent motion stream moves can influence the perceived direction of an auditory apparent motion stream (an effect known as crossmodal dynamic capture). However, little is known about the role that intramodal perceptual grouping processes play in the multisensory integration of motion information.…”
mentioning
confidence: 99%
“…Spatial ventriloquism can also be found with dynamic stimuli. In apparent motion, visual motion direction can attract the perceived direction of auditory motion (Kitajima & Yamashita, 1999;Mateeff, Hohnsbein & Noack, 1985;Soto-Faraco, Lyons, Gazzaniga, Spence & Kingstone, 2002;Soto-Faraco, Spence & Kingstone, 2004a, b, 2005Stekelenburg & Vroomen, 2009), and auditory motion can attract visual motion (Alais & Burr, 2004a;Chen & Zhou, 2011;Meyer & Wuerger, 2001;Wuerger, Hofbauer & Meyer, 2003).…”
Section: Spatial Ventriloquism: Immediate Effectmentioning
confidence: 99%
“…In everyday life, visual motion cues are more reliable and dominate the motion percept. Vision even reverses the perceived direction of a conflicting auditory motion stimulus, a phenomenon referred to as visual capture (Mateeff et al, 1985;Soto-Faraco et al, 2002;Soto-Faraco et al, 2004). However, if the visual stimulus is rendered unreliable, auditory motion can also bias the perception of visual motion direction (Meyer and Wuerger, 2001).…”
Section: Introductionmentioning
confidence: 99%